MULTIMEDIA TECHNOLOGIES TO INCREASE THE QUALITY AND EFFICIENCY OF THE EDUCATIONAL PROCESS - Salomova Malika Zohirovna; Zoxirova Azizabonu Ulugbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article is about the efficiency of using multimedia learning tools in the process of learning foreign languages. The use of modern means, such as awareness programs and Internet technology, as well as cooperative learning and project methodology, allo